(untitled) (Fiep Bulletin - online, 2013)
The aim of the research is to develop the Reiki in the aquatic environment with the aim of defining its use and determine its purpose in the process of energy, emotional and mental. From evaluating the effectiveness of the new method of Aquatic Therapy Water Reiki in various pathologies, it was observed that the union of aquatic therapy and Reiki energy therapy demonstrated, over the period of utilization during this research, effective, thus the unlocking of the points of energy that prevented the circulation of vital energy, provided great relief in pain, stress, depression, promoting greater satisfaction and well-being of individuals in their daily routine. In the study, there were selected ten patients of various pathologies to participate in clinical trials. The patients were divided into two groups. Those who submitted the Water Reiki before being handled by another technique for aquatic therapy, and those who have not had the help of the Water Reiki. Patients were followed for eight weeks with two sessions in each week. Following the practice of Water Reiki, there was a decrease in pain and a considerable improvement, in up to 80%, to the other forms of aquatic therapy as a complement to the treatment. The new technique in question promoted a relief of pain, tension, stress, physical annoyances in body handling during water treatments, and which resulted in well-being, relaxation and greater satisfaction of the patient and also promoted emotional release retained in body memory.